2015
DOI: 10.1002/ange.201504426
|View full text |Cite
|
Sign up to set email alerts
|

A Simple NMR‐Based Method for Studying the Spatial Distribution of Linkers within Mixed‐Linker Metal–Organic Frameworks

Abstract: The spatial distribution of different linkers within mixed-linker metal-organic frameworks crucially influences the properties of such materials.Asimple and robust approach based on 1 Hs pin-diffusion magic-angle-spinning nuclear magnetic resonance measurements and modeling of spindiffusion curves is presented;t his approach facilitates the distinction between homogeneous and clustered distributions. The performance of the approach is demonstrated with an example of an aluminum-based metal-organic material DUT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The distribution of the organic linkers within both crystal and glass phases was also investigated using spin-diffusion NMR spectroscopy. This is a powerful technique which is able to detect the proximity of different organic components based on the rate of polarization transfer between their protons 28,29 . 1 H-detected spin-diffusion experiments were first performed on ZIF-76-mbIm to track the transfer of proton polarization from the methyl group protons of 5-mbIm (resonance at 2 ppm) to all other protons in the sample (with chemical shifts in the region 6-7 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of the organic linkers within both crystal and glass phases was also investigated using spin-diffusion NMR spectroscopy. This is a powerful technique which is able to detect the proximity of different organic components based on the rate of polarization transfer between their protons 28,29 . 1 H-detected spin-diffusion experiments were first performed on ZIF-76-mbIm to track the transfer of proton polarization from the methyl group protons of 5-mbIm (resonance at 2 ppm) to all other protons in the sample (with chemical shifts in the region 6-7 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, synthesis of materials with higher levels of Fe 3+ doping than described here led to the formation of irreproducible amorphous materials. Work carried out by Mali et al in 2015 examined the distribution of linkers in a mixed biphenyl and bipyridyl dicarboxylic acid linker framework, through 1 H and 13 C solid state NMR (SSNMR) experiments [ 61 ]. This work was preluded by Kong et al in 2013, who probed the distribution of functional groups in a mixed-linker framework constructed from six different linkers, using a combination of 1 H, 13 C and 15 N SSNMR experiments, Monte Carlo and molecular dynamics simulations [ 62 ].…”
Section: Functionalisationmentioning
confidence: 99%
“…This valuable information helped them rationalize the observed differences in adsorption capacity and separation efficiency of mixed-linker MOFs characterized by different types of linker distributions. Another approach for studying the distribution of different linkers in mixed-linker MOFs was undertaken by Krajnc et al [22]. They prepared Al-based metal-organic material DUT-5 with biphenyl and bipyridyl dicarboxylic molecules (bpdc and bpydc) as linkers.…”
Section: Framework Structurementioning
confidence: 99%
“…Comparison between the experiment and modeling allowed them to show that in their particular material the distribution of the minority bpydc linker was very homogeneous throughout the crystals and that no single-linker domains or crystallites were formed (see Figure 3). Both studies, the one of Kong et al [21] and the one of Krajnc et al [22], demonstrated that solid-state NMR spectroscopy is indeed a unique tool, capable of providing information that is not attainable by any other technique.…”
Section: Framework Structurementioning
confidence: 99%
See 1 more Smart Citation